The province of Espírito Santo: trade networks and the emancipation of Portuguese America (1815 - 1825) (Ágora Journal, 2022)
The political rupture between Brazil and Portugal was driven not only by events in Rio de Janeiro - seat of the Dom Pedro regency - and in the Lisbon Courts, but also due to different regional circumstances in Portuguese America. In the case of Espírito Santo, the commercial relations of the dealers in this province with ports in Bahia and Rio de Janeiro, since the beginning of the 19th century, were of great importance for local authorities, linked to this interprovincial trade, to decide politically between joining the Cortes or the regency of Dom Pedro, in 1822.